2021
DOI: 10.1159/000512460
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Myometrium Metabolomic Profiles in Labor: Preliminary Results

Abstract: Introduction: Parturition involves multiple complex metabolic processes that supply essential metabolites to facilitate fetal delivery. Little is known about the dynamic metabolic responses during labor. Objective: To profile the changes of myometrial metabolites between nonlabor and labor. Methods: The study involved 30 women in nonlabor and 30 in labor who underwent cesarean section. The characteristics of myometrial metabolite changes during parturition were explored through untargeted metabolomic analysis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In addition to the hypoxic and inflammatory responses, our data also indicated that the upregulated genes radically affected the metabolism, which may be due to cellular responses to hypoxic stress, as labor is an energy-intensive process; an active metabolism can ensure adequate supply of energy. Our previous myometrial metabolomic profile analysis presented an increase in metabolism during delivery, especially in lipolysis and fatty acid oxidation ( 38 ). Other important pathways enriched in the IL myometrium included those involved in hemostasis and extracellular matrix organization.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the hypoxic and inflammatory responses, our data also indicated that the upregulated genes radically affected the metabolism, which may be due to cellular responses to hypoxic stress, as labor is an energy-intensive process; an active metabolism can ensure adequate supply of energy. Our previous myometrial metabolomic profile analysis presented an increase in metabolism during delivery, especially in lipolysis and fatty acid oxidation ( 38 ). Other important pathways enriched in the IL myometrium included those involved in hemostasis and extracellular matrix organization.…”
Section: Discussionmentioning
confidence: 99%
“…3,19 Our previous untargeted metabolomic analysis found that lipolysis and fatty acid oxidation were most significantly increased in in-labor myometrium, compared with non-labor myometrium. 27 In this study, even with hypoxic conditions, SERPINE1 promoted ATP production in hMSMCs mainly by enhancing oxidative phosphorylation, rather than glycolysis. Although studies have shown that increased glycolysis is an important process for ATP supply under hypoxia, particularly in cancer cells 28 and myocytes, 29 the capability of anaerobic metabolism is limited in hMSMCs.…”
Section: Discussionmentioning
confidence: 55%
“…Studies have found that at full term, human myometrium reserves a large amount of energy substances such as glycogen and fatty acid, ATP and phosphocreatine also increased moderately in rat myometrium 3,19 . Our previous untargeted metabolomic analysis found that lipolysis and fatty acid oxidation were most significantly increased in in‐labor myometrium, compared with non‐labor myometrium 27 . In this study, even with hypoxic conditions, SERPINE1 promoted ATP production in hMSMCs mainly by enhancing oxidative phosphorylation, rather than glycolysis.…”
Section: Discussionmentioning
confidence: 92%
“…Labor is an energy-intensive process, and an up-regulation of glucose and lipid metabolism can support the intense contraction of the myometrium. Our previous metabolomic profile analysis of myometrium showed that metabolism increased during labor, especially lipolysis and fatty acid oxidation ( Qian et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%